PRODUCTION OF CETANE IMPROVER FROM Jathropa curcas OIL - Abdullah Abdullah; D.R. Wicakso; A.B. Junaidi; Badruzsaufari Badruzsaufari (Indonesian Journal of Chemistry, 2010)
Nitration of biodiesel from Jatropha curcas oil using mixture of HNO3 and H2SO4 had been done in an attempt to obtain a cetane improver or cetane number enhancer. The nitration was carried out by varying the numbers of moles of sulphuric acid, nitric acid, temperature and time. The process was conducted in a round bottom flask reactor that equipped with a magnetic stirrer and a ball cooler on a water batch. The mixture of H2SO4 and HNO3 was placed in the reactor and subsequently added slowly with biodiesel drop by drop. The results showed that increasing the mole numbers of sulphuric acid tends to reduce the yield or volume and total N of nitrated biodiesel. Increasing the number of moles of nitric acid tends to increase the yield, but decrease the value of total N. While increasing of temperature and reaction time tends to reduce the yield and total N. From FTIR spectra product was estimated as a mixture of esters of alkyl nitrates and nitro. From the testing of cetane number it can be predicted that nitrated biodiesel potentially as cetane improver.